Sistem Informasi Masjid Di Surakarta - Paramita, Claudia, Nurgiyatna, S.T., M.Sc., Ph.D (2016)
Mosque information system website is a group of component and element being combined into one in order to achieve a goal of providing convenience to the society who seeks information about mosques in Surakarta. Before this website is created, the society knows less about the mosque information in Surakarta because previously the society around that mosque and the society that has relationship with the mosques' management are the only ones who know about that. The final result of this website system will provide convenience to the society to get information and to subscribe to the activities of each followed-mosque as well as provide convenience to the Ministry of Religious Affair in Surakarta to monitor the mosques effectively and efficiently. The making of this website uses PHP, MySQL and the interface user uses HTML and CSS. The system was tested by conducting questionnaires website to the public, the board of the mosque, and the Ministry of Religious Affairs Surakarta yield percentage is 93% stating to see on the website is not boring and uncomfortable to be seen. The final result of the system of this website will allow the public to obtain information and subscription activity that followed the mosque as well as facilitate the Ministry of Religious Affairs to monitor mosques Surakarta effectively and efficiently.